Pengaruh Transfer Pricing, Ukuran Perusahaan, dan Komisaris Independen terhadap Agresivitas Pajak : Studi pada Sektor Properti dan Real Estate Tahun 2020-2024 - Ratika Ratika; Inge Lengga Sari Munthe; Teddy Haryadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of transfer pricing, firm size, and independent commissioners on tax aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study is based on Agency Theory and the Theory of Planned Behavior to explain corporate behavior in tax-related decision-making. This research employed a quantitative approach using secondary data obtained from the annual reports of companies listed on the Indonesia Stock Exchange and the official websites of each company. The research sample consisted of nine companies selected through purposive sampling based on predetermined criteria. Multiple linear regression analysis was used to examine the influence of each independent variable on tax aggressiveness. The findings indicate that transfer pricing has no significant partial effect on tax aggressiveness. In contrast, firm size and independent commissioners have a significant partial effect on tax aggressiveness. Furthermore, the coefficient of determination test reveals that transfer pricing, firm size, and independent commissioners collectively explain only 27.8% of the variation in tax aggressiveness, while the remaining 72.2% is influenced by other factors not included in this study. These findings suggest that additional variables should be considered in future research to better explain corporate tax aggressiveness.